NEW MATERIAL USING CEMENT-BASED MATRIX WITH SELF-REPAIR PROPERTIES BASED ON REACTIVE GRAINS WITH PROTECTIVE COATING - ZAPCIU, Miron; VOINIȚCHI, Constantin; IONESCU, Nicoleta; OLTEANU, Marius (Studia Universitatis Babeș-Bolyai Chemia, 2021)
This research relates to cement-based matrix materials with self-repairing properties, based on reactive grains (Portland clinker) having the dimensions 90…160 μm and using a protective coating layer with a thickness of 4-7 μm. The material involves the use in mortars or concretes of a smart additive of a clinker reactive material covered with an impermeable polymeric coating that breaks when a crack appears in the material and allows the reaction between water and cement stone components and, consequently, the formation of a crack plugging product consisting in calcium silicate hydrates gels (CSH), superior to that of calcium carbonate precipitation. The intelligent addition is obtained by mixing the reactive material with the solution of a polymer, or with its melt (C8H8)n. The efficiency of coverage exceeds 80% in most of cases, some of them approaching even 90%. No significant effect of the ratio reactive material/polymer seems to be observed. The degree of healing of the crack is defined in the paper. The method of highlighting the self-repairing effect is based on the amount of electricity passed through the sample. The new material has practically unchanged mechanical properties, a higher hydration capacity and a longer service life-cycle.